(untitled) (Sains Humanika, 2017)
The aim of the present study is to explore the thin line between a learner’s pragmatic failures and styles through their writings and to call for the pragmatic variations of Japanese as a second language in writing such that we establish World Japaneses in the same spirit as World Englishes. In order to achieve this goal, we discuss the role of tutorials in creating a ground of meaning negotiation between peer tutors and students and second the importance of negotiation in choosing the linguistic forms best expressing the non-native students’ ideas rather than automatically conforming to the norms of the native speakers. Specifically, this study offers an ethnographic analysis of writing tutoring sessions between an advanced-level Japanese learner and a native Japanese peer tutor. One of the main findings was the student’s unique use of honorifics when discussing his own home country, which conflicts with native Japanese expectations of honorific use. We suggest examples that need much discussions between the learner and the teacher/tutor at writing conference sessions in order to determine whether it is a pragmatic failure or a student’s style, in the latter a pragmatic variation of World Japaneses. By examining the above-mentioned pragmatic phenomena produced by a L2 writer, we attempt to connect theoretical issues in linguistics, especially Construction Grammar, linguistic ideology, and second language pedagogy